(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Given the importance of arthropods in medical and life sciences and information on the composition of such arthropods in this study was conducted during 2010 in the Kashan. Methods: Descriptive study and sampling at 13 locations and over 39 times in 2303 on the number of larvae, nymphs, Pupa and adults were collected from Lentic and Lotic waters. Samples collected after the transfer to the laboratory using a Stereo microscope and identified using morphological keys used were identified. Results: Total 2303 samples over 39 times the sampling of the Order Diptera, with 1,287 cases (55.8%), crustaceans, with 579 samples (25.2%), Order Trichoptera with 158 samples (6.9%), Order Ephemeroptera 153 samples (6.7%), Order Odonata with 61 samples (2.6%), Order Heteroptera with 26 samples (1.1%), Order Coleoptera with 26 samples (1.1%), Order Plecoptera with 13 sample (0.6) were identified. From Crustacea Class, three orders of the, Amphipoda to 405 numbers (70%) of Lotic water, Ostracoda to 144 (24.9%), Copepoda to 30 (5.1%) from the Lentic waters was collect-ed. Conclusion: In This study, for the first time, from Crustacea subphyllum, order of Ostracoda and Diptera order, Ceratopogonidae, Eryphidae, Dixidae families are reported .Therefore can be concluded that the aquatic arthropods Fauna Kashan is very rich. Considering that some of these insects have a role in the transmission or harassment of human and environmental balance are important, and with molecular methods is recommended that more specific studies done in this field. DOI: http://dx.doi.org/10.3329/bjms.v13i3.15448 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.306-310